2019
DOI: 10.1007/s00429-019-01960-3
|View full text |Cite
|
Sign up to set email alerts
|

The functional microscopic neuroanatomy of the human subthalamic nucleus

Abstract: The subthalamic nucleus (STN) is successfully used as a surgical target for deep brain stimulation in the treatment of movement disorders. Interestingly, the internal structure of the STN is still incompletely understood. The objective of the present study was to investigate three-dimensional (3D) immunoreactivity patterns for 12 individual protein markers for GABA-ergic, serotonergic, dopaminergic as well as glutamatergic signaling. We analyzed the immunoreactivity using optical densities and created a 3D rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 113 publications
6
52
2
Order By: Relevance
“…Some other studies suggest more complex shapes of subregions (e.g., Ewert et al, 2018;Horn et al, 2017; but see Lambert et al, 2012), but there is considerable variability in the reported shapes and even number of hypothesized subdivisions (for review, see Keuken et al, 2012). Other work suggests the STN is organized along a gradient of changes with no clear boundaries (Alkemade et al, 2019;de Hollander et al, 2014). Our approach provides a principled way to formalize the hypothesis that the ventromedial-dorsolateral axis is the most important axis of organization.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some other studies suggest more complex shapes of subregions (e.g., Ewert et al, 2018;Horn et al, 2017; but see Lambert et al, 2012), but there is considerable variability in the reported shapes and even number of hypothesized subdivisions (for review, see Keuken et al, 2012). Other work suggests the STN is organized along a gradient of changes with no clear boundaries (Alkemade et al, 2019;de Hollander et al, 2014). Our approach provides a principled way to formalize the hypothesis that the ventromedial-dorsolateral axis is the most important axis of organization.…”
Section: Discussionmentioning
confidence: 91%
“…All individual STN masks were transformed to the space of the ICBM 152 Nonlinear Asymmetrical template version 2009c (MNI2009c; Fonov et al, 2009). On the mean-subtracted coordinates of the voxels in these masks, we performed a principal components analysis to find the 3D vector (direction) that explained the most variance in the coordinates (Alkemade et al, 2019). We interpreted this vector as the 'main ventromedial-dorsolateral' axis of the STN (de Hollander et al, 2014;Haynes and Haber, 2013;Temel et al, 2005a).…”
Section: Anatomical Labelingmentioning
confidence: 99%
“…Thus, our serial smFISH, immunostaining, and topographic analysis confirmed that most neurons in the STN are purely glutamatergic. Previous anatomical studies have reported the presence of parvalbumin-expressing (PV+) neurons in the STN (Alkemade et al, 2019; Hontanilla et al, 1998; Lévesque and Parent, 2005; Wu et al, 2018). PV expression is conventionally interpreted to reflect a GABAergic subpopulation (Hu et al, 2014), which is inconsistent with our serial smFISH results and previous studies (Lévesque and Parent, 2005; Roccaro-Waldmeyer et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This amplifies the question raised by Alkemade and Forstmann (2014) challenging the tripartite theory of the STN described above. Recent studies have also challenged this idea showing that the STN may in fact be a heterogeneous structure with no clear inner boundaries, where neurons are dynamically adapting and respond to very specific input information (Alkemade et al., 2019). This shows that it is probably very important to account for cognitive confounding factors in studies of sensorimotor beta in STN.…”
Section: Discussionmentioning
confidence: 99%